Durkheim, Germany, War, Europe - Karsenti, Bruno (Simmel Studies, 2018)
Among the classical authors of sociology, Émile Durkheim passed away the first on 15 November 1917. His conception of the war as well as his ideas of a possible way out of it, therefore, are far from the horizon of experience that characterized the last year of the conflict. His major war writing is a critical analysis of the intellectual sources of German militarism: L’Allemagne au-dessus de tout. Karsenti focuses on Durkheim’s examination of the “Über-Ideology”, which moulded German nationalism since unification in 1871, especially in the work of Heinrich von Treitschke. Durkheim’s book is a censorship of the enemy’s warfare. Yet, what is interesting to discover, according to Karsenti, is the particular perspective of Durkheim’s investigation. The writing is a critique of all tendencies to reduce international politics to an “Über”. Accordingly, for Durkheim, there is a possible way out of the war, yet it has to be read between the lines of his distinction between a “good and a bad tradition” of the moral sciences in Germany.